Сучасні погляди на філогенію та положення родини Orchidaceae Juss. у системі однодольних рослин - Mosyakin, S.L.; Buyun, L.I. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2006)
The article provides an overview of recent publications devoted to phylogeny and taxonomy of the family Orchidaceae Juss., with a special reference to molecular phylogenetics. Modern methods of molecular taxonomy and phylogenetics are powerful tools that clarified many long-debated problems in phylogenetic systematics of orchids. In the recent phylogenetic systems (APG, APG II and others) Orchidaceae are placed in or near the extended order Asparagales, most probably at the base of the asparagalean clade. Recent age estimations for major angiosperm groups yielded rather unexpected results indicating that the orchid clade might be among the most ancient clades of extant monocots (molecular clock estimations at ca. 110 millions years). Ancestral orchids were probably terrestrial plants, and the epiphytic habit developed in the family many times and independently in different groups. The currently accepted topology of the phylogenetic tree of Orchidaceae indicates five major clades corresponding to subfamilies Apostasioideae, Vanilloideae, Cypripedioideae, Orchidoideae, Epidendroideae. Many traditionally accepted genera proved to be polyphyletic or paraphyletic, which will result in many taxonomic and nomenclatural changes. Special studies of morphological, biogeographical and other peculiarities of critical taxa are needed to explain the newly discovered molecular phylogenetic patterns in orchids.